Proceso de atención de enfermería en paciente de sexo femenino de 67 años de edad con Covid-19. - Martínez Vidal, Vanessa Dianella (2020)
The global health emergency caused by the current Covid-19 pandemic is probably posing one of the greatest challenges that healthcare professionals have faced throughout their careers is the infectious disease caused by the coronavirus that has been most discovered Recently. Both this new virus and the disease it causes were unknown before the outbreak broke out in Wuhan, China, in December 2019. Currently, COVID-19 is a pandemic that affects many countries around the world. In order to better understand the scope and impact of this problem, a review of the clinical case was carried out in a 67-year-old patient diagnosed with COVID-19, a follow-up is carried out from its onset until she presented improvement.